Pigmentary mosaicism with recurrent inflammation and hemiparesis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
The distribution of skin lesions according to the Blaschko lines indicates the presence of a mosaicism, i.e. two cell lines, and is an expression of migration faced by the ectodermal cells during the embryonic life. The condition of mosaicism may be clinically apparent from the first periods of life, as in ncontinentia pigmenti, hypomelanosis of Ito, epidermal nevi and pigmentary mosaicism or remain clinically silent until environmental factors highlight it, as is the case of acquired skin disorders (lichen striatus, linear psoriasis, ecc.). At the base of the cutaneous mosaicism there is a chromosomal mosaicism: this has been demonstrated for the first time in hypomelanosis of Ito (2), but it is likely that all patients with pigmentary mosaicism have a chromosomal mosaicism, although this can be detected only in 25% of cases (5) as numerical alterations of chromosomes, gross structural alterations as deletions, insertions, translocations and point alterations. The percentage of cases which prove to be a chromosomal mosaicism increase when you go to look not only in fibroblasts but also in cultured keratinocytes (3). Our case associated neurological lesions to those of the skin, which is the most frequent association in case of clinically extensive mosaicism. Its frequency is justified by the common source of skin and CNS from the neural crest. The association with neurological lesions and the distribution of the pigmented lesions were reminiscent of incontinentia pigmenti. The suspect of incontinentia pigmenti was also favored by the periodic inflammatory flares up during infectious episodes, which have been described mainly in incontinentia pigments (4), but also in focal dermal hypoplasia or Goltz syndrome (1). However, the absence of inflammatory and warty lesions before the advent of pigmentation, the absence of a family history and the negativity of the research of NEMO gene deletions deposed against the diagnosis of incontinentia pigmenti and then led to the diagnosis of pigmentary mosaicism.